Reading Victorian Deafness : Signs and Sounds in Victorian Literature and Culture - Esmail, Jennifer, 1979- (Book collections on Project MUSE., 2013)
Reading Victorian Deafness is the first book to address the crucial role that deaf people, and their unique language of signs, played in Victorian culture. Drawing on a range of works, from fiction by Charles Dickens and Wilkie Collins, to poetry by deaf poets and life writing by deaf memoirists Harriet Martineau and John Kitto, to scientific treatises by Alexander Graham Bell and Francis Galton, Reading Victorian Deafness argues that deaf people's language use was a public, influential, and contentious issue in Victorian Britain. The Victorians understood signed.